2012
DOI: 10.1007/s11101-012-9254-4
|View full text |Cite
|
Sign up to set email alerts
|

Botanical nematicides in the mediterranean basin

Abstract: Achieving food sufficiency in a sustainable manner is a major challenge for farmers, agro-industries, researchers and governments. Amongst agricultural pests supressing crops, root-knot nematodes (Meloidogyne spp.) represent possibly the world's most damaging one, the control of which has been mainly based on chemical nematicides. In the recent years the environmental, food safety and animal welfare issues pose the need for alternative nematode control measures. Screening naturally occurring compounds in plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 43 publications
0
23
0
1
Order By: Relevance
“…Botanical nematicides have attracted considerable interest in recent years . Single nematicidal compounds could be used directly after purification of botanical extracts or can serve as prototypes in the chemical synthesis of nematicidal formulates, whereas the nematicidal botanical extracts could be produced and applied directly by the farmer on the field as an ecofriendly, cost‐effective nematode control method.…”
Section: Discussionmentioning
confidence: 99%
“…Botanical nematicides have attracted considerable interest in recent years . Single nematicidal compounds could be used directly after purification of botanical extracts or can serve as prototypes in the chemical synthesis of nematicidal formulates, whereas the nematicidal botanical extracts could be produced and applied directly by the farmer on the field as an ecofriendly, cost‐effective nematode control method.…”
Section: Discussionmentioning
confidence: 99%
“…(marigolds) are often effective in the management of both root‐knot nematodes and related soil diseases because of their biofumigation potential, i.e. their release of volatile toxic secondary metabolites or degradation products …”
Section: Introductionmentioning
confidence: 99%
“…As a promising alternative to chemical nematicides, research on the botanical nematicide is receiving increasing attention . The current study found that crude extract of W. indica roots has strong nematocidal activity against J2 of M. incognita.…”
Section: Discussionmentioning
confidence: 97%